HUBUNGAN PRESTASI AKADEMIK DENGAN RIWAYAT PEMBERIAN ASI PADA ANAK - Tity Wulandari (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2019)
Breast milk is milk which produced by mother's breast glands for infants consumption and is the main source of nutrition for infants who have not been able to digest solid foods. This research is motivated by the problems of many mothers who switched to using formula milk instead of breastfeeding their children. The purpose of this study to find the relationship of academic achievement with history of breast milk in children in Elementary School 060818 Medan City District. This research use analytical method with cross sectional design approach. The measuring tool used is questionnaire. The population of this study are the students of Elementary School 060818 Medan City District. The sampling was taken on the 5th and 6th graders,there were 82 students who meet the inclusion criteria. Data to be analyzed using independent t-test. The results showed that students who consumed exclusive breastfeeding were 26 student (31.7%) and who did not consume exclusive breastfeeding were 56 student (68.3%).Average academic achievement of children who consumed exclusive breastfeeding 73.6 and the average achievement of children who did not consume exclusive breastfeeding 74.9. Based on the results of statistical tests using independent t-test, p = 0.35,it is concluded that there is no significant difference at academic achievement between the exclusive breastfeeding and the formula milk students.